2011
DOI: 10.1266/ggs.86.141
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of chromosomal DNA replication in eukaryotic cells; contribution of yeast genetics to the elucidation

Abstract: Chromosomal DNA replication is a fundamental process in the transmission of genetic information through generations. While the molecular mechanism of DNA replication has been studied for a long time, knowledge regarding this process in eukaryotic cells has advanced rapidly in the past 20 years. Yeast genetics contributed profoundly to this rapid advancement. Reverse genetics and genetic screenings identified all genes encoding replication proteins in budding yeast. Moreover, the genetic interactions that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 66 publications
(83 reference statements)
0
15
0
Order By: Relevance
“…At the G1/S transition, this prereplication complex is altered further by a number of replication initiation factors whose actions are facilitated by the cyclin-dependent and cell division cycle 7 (Cdc7)-dumbbell former 4 (Dbf4) kinases (4). These replication initiation factors [which include synthetically lethal with dpb11-1 (Sld)2, Sld3, Sld7, DNA polymerase B possible subunit 11 (Dpb11), and DNA polymerase e (Pol e) in budding yeast] play critical roles resulting in the interaction of Cdc45 and GINS with the Mcm2-7 complex and the formation of the replicative DNA helicase complex containing Cdc45/Mcm2-7/GINS (CMG) (5). Other replication factors (including Mcm10 and Ctf4) contribute to the activation of the CMG helicase and association of proteins that recruit the replicative Pols to effect DNA replication (6,7).…”
mentioning
confidence: 99%
“…At the G1/S transition, this prereplication complex is altered further by a number of replication initiation factors whose actions are facilitated by the cyclin-dependent and cell division cycle 7 (Cdc7)-dumbbell former 4 (Dbf4) kinases (4). These replication initiation factors [which include synthetically lethal with dpb11-1 (Sld)2, Sld3, Sld7, DNA polymerase B possible subunit 11 (Dpb11), and DNA polymerase e (Pol e) in budding yeast] play critical roles resulting in the interaction of Cdc45 and GINS with the Mcm2-7 complex and the formation of the replicative DNA helicase complex containing Cdc45/Mcm2-7/GINS (CMG) (5). Other replication factors (including Mcm10 and Ctf4) contribute to the activation of the CMG helicase and association of proteins that recruit the replicative Pols to effect DNA replication (6,7).…”
mentioning
confidence: 99%
“…[1][2][3][4] The function of MCM2-7 is regulated by various proteins. CDC45 binds to MCM2-7 with GINS complex to form CMG complex, and the cumulative data suggest that the CMG complex functions as a DNA helicase at the forks.…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of the role of CDK in replication initiation was greatly advanced by synthetic lethal genetic screens conducted by H. Araki and colleagues in the budding yeast Saccharomyces cerevisiae (Araki 2011;Kamimura et al 1998;. These screens utilised hypomorphic alleles of an essential replication factor called Dpb11, which has four BRCA1 C terminus (BRCT) repeats that act as phosphopeptide-binding domains.…”
Section: Introductionmentioning
confidence: 99%
“…These screens utilised hypomorphic alleles of an essential replication factor called Dpb11, which has four BRCA1 C terminus (BRCT) repeats that act as phosphopeptide-binding domains. From these synthetic lethal with dpb11 (SLD) screens, several new replication factors were identified, including two genes SLD2 and SLD3 (Araki 2011). Subsequent studies showed that both Sld2 and Sld3 are essential targets of CDK in budding yeast (Masumoto et al 2002;Tanaka et al 2007;Zegerman and Diffley 2007).…”
Section: Introductionmentioning
confidence: 99%